2018
DOI: 10.3389/fcimb.2018.00359
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Flaviviridae in Mosquito Viromes Isolated From Yunnan Province in China Reveals Genes From Dengue and Zika Viruses

Abstract: More than 6,000 mosquitoes of six species from six sites were collected and tested for their virome using metagenomics sequencing and bioinformatic analysis. The identified viral sequences belonged to more than 50 viral families. The results were verified by PCR of selected viruses in all mosquitoes, followed by phylogenetic analysis. In the present study, we identified the partial dengue virus (DENV), Zika virus (ZIKV), and Japanese encephalitis virus (JEV) sequences in mosquitoes. Metagenomic analysis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…In order to ensure comparability with what humans receive, future studies may need to test various dosing regimens. Fu et al and Xiao et al identified ZIKV in mosquitoes in Guizhou province and Yunnan province (Fu et al 2017;Xiao et al 2018), indicating that ZIKV is present in China. Therefore, it is inevitable that JEV and ZIKV co-circulate.…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure comparability with what humans receive, future studies may need to test various dosing regimens. Fu et al and Xiao et al identified ZIKV in mosquitoes in Guizhou province and Yunnan province (Fu et al 2017;Xiao et al 2018), indicating that ZIKV is present in China. Therefore, it is inevitable that JEV and ZIKV co-circulate.…”
Section: Discussionmentioning
confidence: 99%
“…and Xiao et al . identified ZIKV in mosquitoes in Guizhou province and Yunnan province (40, 41), indicating that ZIKV is present in China. Therefore, it is inevitable that JEV and ZIKV co-circulate.…”
Section: Discussionmentioning
confidence: 99%
“…S2B). This level of sensitivity was achieved by using a customised mosquito rRNA depletion, which helped to achieve a higher portion of viral sequencing reads (11.7-17.3%) compared to other metatranscriptomic studies where mosquito pool samples had as little as <1% viral reads [45][46][47] . Notably, the rRNA depletion was effective only when a higher concentration of the customised probe mixture was used than advised in the manufacturer's instructions (Fig.…”
Section: Discussionmentioning
confidence: 99%